2023
DOI: 10.3847/1538-4357/acac76
|View full text |Cite
|
Sign up to set email alerts
|

Unified Relationship between Cold Plasma Ejections and Flare Energies Ranging from Solar Microflares to Giant Stellar Flares

Abstract: We often find spectral signatures of chromospheric cold plasma ejections accompanied by flares in a wide range of spatial scales in the solar and stellar atmospheres. However, the relationship between physical quantities (such as mass, kinetic energy, and velocity) of cold ejecta and flare energy has not been investigated in a unified manner for the entire range of flare energies to date. This study analyzed the spectra of cold plasma ejections associated with small-scale flares and solar flares (energy 1025–1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Figure 8(a) indicates that the erupted prominence on V1355 Orionis has roughly the mass that expected from the scaling law of solar CMEs. This suggests that the prominence eruption on V1355 Orionis was caused by the same physical mechanism as the solar prominence eruptions/CMEs (e.g., Kotani et al 2023). Figure 8(a) also shows that it is the largest prominence eruption observed by blueshift.…”
Section: Comparison With Other Eventsmentioning
confidence: 77%
“…Figure 8(a) indicates that the erupted prominence on V1355 Orionis has roughly the mass that expected from the scaling law of solar CMEs. This suggests that the prominence eruption on V1355 Orionis was caused by the same physical mechanism as the solar prominence eruptions/CMEs (e.g., Kotani et al 2023). Figure 8(a) also shows that it is the largest prominence eruption observed by blueshift.…”
Section: Comparison With Other Eventsmentioning
confidence: 77%
“…, based on the assumption that the flare radiation energy E WL,bol ∼ 10 35 F GOES should be roughly less than CME kinetic energy Kotani et al (2023) suggested that the power-law index for the relation between erupted mass and flare energy scale is the same for CMEs and prominence eruptions, i.e., M F GOES 2 3 µ ; therefore, a similar scaling law for the upper limit of the prominence velociy V p can be also derived by following Takahashi et al (2016):…”
Section: • ( ) ( ) = mentioning
confidence: 99%
“…Our results suggest that, like solar CMEs/filament eruptions, the ejected mass against a given flare energy scale exhibits considerable scattering in the case of young Sun-like stars, spanning one to two orders of magnitude. Kotani et al 2023 theoretically suggested that the scattering may be explained by difference in magnetic field strength supporting the prominence. Hence, our findings in diversity in mass (and kinetic energy below) may be related to the diversity in the local magnetic field strength of the star.…”
mentioning
confidence: 94%
See 2 more Smart Citations